EVALUATION OF INFORMATICS TEACHING REALISATION IN SLOVAKIA AND CZECH REPUBLIC AS AN INTEGRAL PART OF TECHNICAL EDUCATION - HASKOVA, Alena; ZAHOREC, Jan (Trends in education, 2012)
Computer literacy represents one of the pillars, technical education is based on. At upper secondary schools this literacy is formed and developed mainly within computer science/informatics education. In the paper there are presented methodological basis and the most important and outstanding results of a research aimed at evaluation of selected aspects of informatics teaching realisation done from the students' point of view, specifically students of secondary grammar schools. The research was carried out separately for the Slovak and Czech Republic, and so in the paper there are discussed also the identified common points and differences in the evaluation of the observed aspects of the quality of teaching informatics in both countries.
Keywords: informatics/computer science; evaluation of quality of the teaching; strengths and weaknesses of teaching process.